Hypertension and Obesity in Male Bus Drivers - (:unkn) unknown (ORTADOGU AD PRES & PUBL CO, 2009)
Objective: The purpose of this study was to investigate the prevalence of hypertension, obesity and associated factors in male bus drivers working in Istanbul, Turkey. Material and Methods: This study was designed as a cross-sectional survey. An the bus drivers (n= 4261) employed by the municipality of Istanbul were examined by primary care physicians and were referred to specialists when necessary. A questionnaire regarding the socio-demographic characteristics, health history and lifestyle factors was filled by face-to-face interviews and health data were collected through detailed physical examinations, lab tests, blood pressure and height-weight measurements. Results: The overall prevalence of hypertension in the study group was 31.4%. Hypertension prevalence increased significantly with age and body mass index (BMI) of the drivers. Prevalence rate was 23.6% among younger bus drivers (< 35 years old), and 42.2% among older participants (>= 50 years old). Crude prevalence rate was significantly lower among the underweight than among obese bus drivers (14.8% and 47.1% respectively, p< 0.001). However, age-adjusted prevalence rates were not significantly different (30.4% and 31.8% respectively, p> 0.05). Multivariate analysis of the survey data indicated that BMI and age were the most significant predictors of hypertension among male bus drivers. Conclusion: The hypertension prevalence in our study group was slightly higher than the prevalence rates estimated for the global adult male population and the male hypertension rate found in a recent national survey in Turkey. We concluded that weight control and health education could be helpful to reduce hypertension in this high-risk group.
Keywords: Epidemiology; hypertension; obesity; prevalence; CORONARY-HEART-DISEASE; BLOOD-PRESSURE; PREVALENCE; MORTALITY; RISK; POPULATION; AWARENESS; WEIGHT; COHORT; MEN